The prevalence of post-traumatic stress disorder in college students by continents and national income during the COVID-19 pandemic: a meta-analysis - Hu, Biao; Yang, Xiling; Tuo, Xiaoqian (Frontiers in Psychology, 2023)
The present study aimed to provide a more accurate representation of post-traumatic stress disorder (PTSD) in college students during COVID-19 by performing meta-analyses by continents, national income, and study majors, and comparing the results with estimated pooled prevalence. Based on the guideline of PRISMA, literature was searched in PubMed, Web of Science, and Embase. The prevalence of PTSD was estimated through a random model based on the different continents and levels of national income, as well as study majors, and compared with the pooled prevalence of PTSD among college students. The results showed that the pooled prevalence of college students’ PTSD was 25% (95% CI: 21-28%). Prevalence estimates of PTSD among college students were statistically significant (P<0.00001) when stratified with geographical regions, income levels, and study majors. In comparison with the pooled prevalence of PTSD (25%), subgroups of Africa and Europe, lower-middle-income countries, and medical college students possessed higher prevalence estimates. The findings of the study showed that the prevalence of PTSD in college students worldwide during COVID-19 was relatively high and varied in different continents and countries with different income levels. Therefore, healthcare providers should pay attention to the psychologically healthy condition of college students during COVID-19.